Майнова політика радянського керівництва на початку 1920-х рр. (на прикладі міста Чернігова) - Непотенко, І. (Сiверянський лiтопис, 2015)
Стаття присвячена політиці вилучення майна у городян і побутуванню місцевих
жителів у ході її реалізації. Крім того, схарактеризовано умови, в яких здійснювалася
конфіскація, а також розкрито заходи комітету охорони пам’яток старовини та
мистецтва, вжиті для збереження культурних цінностей. Статья посвящена политике изъятия имущества у горожан, бытованию местных
жителей в процессе ее реализации. Кроме того, охарактеризованы условия, в которых осуществлялась конфискация, а также раскрыто мероприятия комитета охраны памятников старины и искусства, предпринятые для сохранения культурных ценностей. After the hostilities of 1918-1919 and transition to a peaceful life it was found out that
the level of providing needs of the greatest part of the urban people was poor. A lot of citydwellers,
especially the poorest of them, among others, were in a dire need of clothing and shoes.
In addition, after opening of many Soviet institutions the need of furnishing them arose. The
new Soviet leadership decided to solve the problem partially at the expense of confiscation
of clothing and furniture. The norms of things that were allowed to own were introduced. All
things that were above the norm were seized. It concerned the furniture, clothing and footwear,
jewelry and musical instruments. Primarily the confiscation of property dealt with the rich
citizens, as well as the middle class, Nepmen and bourgeoisie – people in relation to whom the
Soviet power had a hostile attitude. However, the majority of city residents were gradually
covered by it. The property of urban residents had to be recorded. Then the «excessive»
property, luxury goods and jewelry owned by residents, as well as items that were not in their
permanent use were defined. The confiscation did not apply for certain categories of people
(Red Army soldiers, educators) if they had certificates. The militiamen and Extraordinary
Commission carried out the searches in the houses of the residents of Chernihiv in order to
identify the property that was not declared. Besides, the Provincial Executive Committee and
Provincial Food Committee conducted the confiscation of property. Chernihiv city-dwellers
resorted to various ways of hiding the property – in their own houses, neighboring estates
because they did not want to give it voluntarily. A lot of confiscated things had artistic and
historical value. The Committee of preservation of monuments of art and antiquities did some
measures for its conservation.